PEMERIKSAAN KADAR ASAM URAT DARAH PADA LANSIA DENGAN METODE STICK DI PUSKEMAS TANJUNG REJO KECAMATAN PERCUT SEITUAN - Geminsah Putra Halomoan Siregar; Fadli Fadli (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Uric acid is a substance of the end result of purine metabolism in the body. Excess uric acid will not be accommodated and completely metabolized by the body. Elderly age is sixty years old and above. The purpose of this study was to d etermine Uric Acid Levels Stick Method In Elderly in Public Health Center Tanjung Rejo Sub District of Percut Sei Tuan. The examination method is Stick. Experiment test is descriptip the results of the examination stick method from March-Mei increased uric acid levels of 71 samples (53%) of the 71 samples total populations examined and the percentage of normal levels of uric acid that is 33 samples (47%). Judging from the results of the percentage of uric acid levels were checked on the elderly in Center Of Public Health Tanjung Rejo Sub District of Percut Sei Tuan, Distric Deli Serdang regency have a tendency to increased levels of uric acid in the blood. To avoid an increase in uric acid levels of the elderly should consult with a doctor, a healthy lifestyle and reduce the consumption of foods high in purines and follow the Prolansia’s program that have been applied by government for improving the quality of healthcare elderly